A study of sustainable management of solid waste in Perhentian island, Malaysia - Jumadil Saputra, Siti Aisyah Saat, (Opción, 2019)
This paper examines plans for the sustainable management of solid waste and the challenges faced by the local municipal and chalet owners in Perhentian Island, Malaysia. The study adopts a qualitative design involving in-depth interviews with five informants. The results outline a strategy to improve the current waste management plan such as focusing on composting and recycling as more economical and environmentally-friendly approaches to waste management. In conclusion, the local authority administering the island is now looking for a better way of managing this waste.